Depicting of DNA Makeup of Wheat Genotypes Using SSR Markers and Their Association with Thermotolerance - Amin, Md Forhad; Alam, Mohammad Nur; Rahman, Aminur (Bangladesh Journal of Agriculture, 2025)
Wheat, a crop highly sensitive to temperature, faces increased risks due to global warming. This study aimed to analyze DNA to identify wheat genotypes that respond well to heat and to uncover genetic similarities and differences among them. Fifteen wheat genotypes were planted on two dates, November 21 (Irrigated Timely Sowing, ITS) and December 21 (Irrigated Late Sowing, ILS), and analyzed with 13 SSR markers. A dendrogram divided the genotypes into two primary groups, each containing four sub-clusters. The greatest genetic distances were observed between BAW 1290 and BARI Gom 28 (0.929), while the smallest genetic distance (0.000) was found between Nadi 2 and BAW 1147. These results suggest that genotypes in both Cluster I and Cluster II (Group A) display moderate tolerance to heat, as indicated by their Heat Susceptibility Index (HSI) for 1000-grain weight (TGW) and grain yield, with HSI values between 0.50 and 1.00, allowing them to perform under heat stress. In contrast, genotypes in Group B, especially those in Cluster III, showed higher HSI values (1.04-1.23) and significant declines in TGW and yield under heat, indicating susceptibility. Similarly, Cluster IV genotypes exhibited heat sensitivity (HSI>1.00). Seven genotypes, specifically BARI Gom 33, BARI Gom 32, BARI Gom 31, BARI Gom 30, BARI Gom 29, BARI Gom 26, and BARI Gom 25 were identified as suitable for cultivation under heat stress. These findings and other studies on heat-tolerant genotypes are valuable for advancing heat-resilient breeding programs based on SSR marker selection. Bangladesh J. Agri. 2025, 50(1): 20-35